2021
DOI: 10.1177/2152656721989287
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Odontogenic Pathology in Patients With Bilateral Rhinosinusitis

Abstract: Objective We investigated cases with opacification on maxillary sinus computed tomography (CT) among patients with rhinosinusitis with opacification in both paranasal sinuses (bilateral rhinosinusitis) to confirm the involvement of odontogenic infections. Methods This study included 75 patients who were diagnosed with bilateral rhinosinusitis based on clinical examination and evident opacification on at least one side on maxillary sinus imaging with computed tomography CT. The definition of odontogenic sinusit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
4
1
Order By: Relevance
“…As some reports suggest that dentists cannot distinguish odontogenic sinusitis through dental symptoms, such as pain and dental hypersensitivity, it may also be difficult for otolaryngologists to diagnose using only nasal symptoms (3,11) . Our data showed the 1st molar was most infiltrated to the maxillary sinus, though various other reports showed the 2nd molar was most infiltrated to the maxillary sinus (10,12,13) . Both 1st and 2nd molars were recognized as the origin of infection in two patients.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…As some reports suggest that dentists cannot distinguish odontogenic sinusitis through dental symptoms, such as pain and dental hypersensitivity, it may also be difficult for otolaryngologists to diagnose using only nasal symptoms (3,11) . Our data showed the 1st molar was most infiltrated to the maxillary sinus, though various other reports showed the 2nd molar was most infiltrated to the maxillary sinus (10,12,13) . Both 1st and 2nd molars were recognized as the origin of infection in two patients.…”
Section: Discussioncontrasting
confidence: 66%
“…Our data suggested that multiple molars could be the cause of the odontogenic sinusitis simultaneously. Dental doctors could not distinguish that either one was specific for the infection site because both molars' inflammation sites were obviously seen to involve the floor of the maxillary sinus (10) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These symptoms are nonspecific and would not help in the diagnosis of odontogenic sinusitis [ 27 ]. Although odontogenic sinusitis usually presents as unilateral maxillary rhinosinusitis, Matsumoto et al found odontogenic infections in 45.3% of bilateral rhinosinusitis patients [ 28 ]. Therefore, screening for a possible odontogenic focus in CRS is extremely important.…”
Section: Discussionmentioning
confidence: 99%
“…The septa of the maxillary sinus are composed of cortical bone that divides the floor of the sinus into multiple chambers known as recesses. 1 During surgical procedures like implants, the risk of perforation of the floor increases if there are anatomic variations within the maxillary sinuses, such as septa, mucosal thickening of the sinus floor, or others. A study conducted by Raghav et al, 2 recorded the presence of a high rate of incidental maxillary sinus abnormalities in a sample of asymptomatic dental patients.…”
Section: Introductionmentioning
confidence: 99%